Valuasi Ekonomi Untuk Obyek Wisata Di Pantai Menganti Kebumen Jawa Tengah - Desti Ayuditya; Rifki Khoirudin (EKONOMI & SOSIAL, 2022)
Giving value (economic valuation) at Menganti beach becomes an important assessment in line with rumors about plans for the development of facilities and infrastructure that are quite large by the manager in the future, which are feared to have an impact on changes in the economic potential in terms of the use value of this beach. The analytical tool used to determine the variables that affect the number of visits and to find the estimated economic value of Menganti beach is the Individual Travel Cost Method. This research was conducted at the Menganti Beach tourist attraction in the village of Karangduwur, Ayah District, Kebumen Regency. The object of this research is the visitors who come to Menganti Beach. The type of research conducted is descriptive quantitative research. This study uses the dependent variable (Y) and independent variables in the form of Travel Costs (X1), Income (X2), Access (X3), Facilities (X4). Sampling in this study used a non-probability sampling method, namely purposive sampling with a sample of 100 respondents. Based on the research conducted, it is known that access and facilities variables have a significant effect on the number of visits to Menganti beach. The consumer surplus obtained by visitors is Rp. 2,971,348.37. While the economic value of Menganti beach is Rp. 1,366,820,250,200 per year with an average WTP value of visitors is Rp. 30,714.